â€œTHE DESTINY OF A GOOD LISTENER?â€ A DECONSTRUCTIVE READING OF A SHORT STORY NASIB SEORANG PENDENGAR SETIA BY JUJUR PRANANTO - Akun, Andreas (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2009)
A literary text is open to signification process by any readers and it is just possible that the text has contesting forces that are at the same time contradictory each other even within the same text. This study attempts to deconstructively read a short story Nasib Seorang Pendengar Setia by Jujur Prananto to reveal the contradiction, inconsistency and unreliability of the text that evidently constitute the warring forces inside the story. This is a library research by applying deconstructive reading method as proposed by Jacques Derrida to show the verbal, textual and linguistic ambiguity and unreliability of the text. The result of the study shows that the short story in the light of deconstructive reading is undoubtedly containing quite many contradictions and inconsistencies that climax in the fact that the content of the story betrays its intended main idea and the title.